An energetic approach for the prognosis of thermally induced white etching layers in bearing steel 100CrMn6. (March 2020) - Gutiérrez Guzmán, F.; Sous, C.; van Lier, H.; Jacobs, G.
Abstract: Thermally induced white etching layers (WEL) are known to increase the risk of rolling contact fatigue (RCF) cracks. This study focuses on the potential of an energetic approach for the prognosis of thermally induced WEL in oil-lubricated rolling/sliding contacts. For the determination of power and energy density thresholds a laser surface treatment was selected. The thresholds were determined using non-lubricated flat specimens made of 100CrMn6 bearing steel. The applicability of the energetic approach for the prognosis of WEL appearance in oil-lubricated rolling/sliding contacts was shown using a two-disc test rig. The formation of WEL was achieved by an acceleration process under varying contact parameters such as speed and load. The appearance of WEL was confirmed through metallographic investigations. Highlights: Formation of white etching layers (WEL) in flat specimens through laser treatment. Formation of WEL in oil-lubricated rolling/sliding contacts in a two-disc test rig. Definition of an energetic approach to predict the appearance of WEL. Assessment of the influence of varying contact conditions on WEL formation. Metallographic characterization of affected components.